Effects of drying methods on bioactive components of Ganoderma lucidum fermented whole wheat in products & in vitro digestive model. (June 2023) - Li, Yang; Gu, Fengying; Guo, Xin; Zhang, Qiaozhen; Hu, Runrun; Qin, Ling; Wang, Qiang; Wang, Feng
Graphical abstract: Highlights: Vacuum drying is suitable for Ganoderma lucidum fermented whole wheat (GW) drying. Medium-temperature drying favored the retention of polysaccharide and adenosine in GW. Microwave processing improved the content of ergosterol and phenolics in GW. Phenolics and adenosines from GW were primarily released in the stomach. The structure of mycelium and starch was affected by drying methods. Abstract: The content of bioactive components is the key to determining the quality of Ganoderma lucidum fermented whole wheat (GW) products, and drying is a necessary link in the initial processing of GW, which will affect the bioactivity and quality of GW. This paper was to assess the effect of hot air drying (AD), freeze drying (FD), vacuum drying (VD) and microwave drying (MVD) on the content of bioactive substances and the characteristics of digestion and absorption of GW. The results showed that FD, VD and AD were beneficial to the retention of unstable substances such as adenosine, polysaccharide and triterpenoid active components in GW, and their contents were 3.84–4.66 times, 2.36–2.83 times and 1.15–1.22 times of MVD, respectively. The bioactive substances in GW were released during digestion. The bioavailability of polysaccharides in the MVD group (419.91 %) was significantly higher than that in the FD, VD and AD groups (68.74 %–78.92 %), but their bioaccessibility (5.66 %) was lower than that in the FD, VD and AD groups (33.41 %–49.69 %). Principal component analysis (PCA) showed that VD is more suitable for GW drying due to the comprehensive performance of 3 aspects in terms of active substance retention, bioavailability and sensory quality.